Trades access common core. Line C, Tools and equipment, Competency C-2, Describe common power tools and their uses - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Power tools play a major role in virtually every trade. You will be expected to be familiar with a wide range of portable and stationary power tools and to understand the safe operation of these tools. Proper maintenance improves the life and performance of the tool. Correct set-up and operating procedures ensure good results and prevent injury. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line C - Tools and Equipment. C-1 Describe Common Hand Tools and Their Uses, C-2 Describe Common Power Tools and Their Uses, C-3 Describe Rigging and Hoisting Equipment, C-4 Describe Ladders and Platforms."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Power tools -- Textbooks; Electronic books